Diverging Trends in Aggregate and Firm-Level Volatility in the UK - Miles Parker (Bank of England, External Monetary Policy Committee Unit, 2006)
This paper documents an increase in the volatility of output at the firm level in the United Kingdom, in keeping with recent research for the United States. Evidence at the sectoral level suggests that this may have arisen as a result of increased product market competition. This greater volatility at the firm level has also occurred at a time of greater macroeconomic stability, commonly referred to as the 'Great Stability'. National accounts data for 31 sectors in the economy show that the fall in aggregate volatility is mostly a result of lower covariance between sectors rather than individual sectors becoming less volatile. This suggests a possible role for structural change in explaining the causes of the 'Great Stability'.
Keywords: 330